ANCIENT CITIES - RICHES OF NATIVE LAND - Abduhamidova Odinaxon Rahmonberdievna,; Rahmonberdieva Kxilola Dilshodjon kizi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article is about the ancient cities of Uzbekistan.